Divergent Reassortment and Transmission Dynamics of Highly Pathogenic Avian Influenza A(H5N8) Virus in Birds of China During 2021 - Ye, Hejia; Zhang, Jiahao; Sang, Yunfen; Shan, Nan; Qiu, Weihong; Zhong, Wenting; Li, Junbao; Yuan, Zhaoxia (Frontiers in Microbiology, 2022)
Highly pathogenic influenza A(H5N8) viruses had caused several outbreaks among wild bird and poultry populations across the globe, and strikingly, caused human infection, posing serious public health concerns. In this study, we conducted influenza surveillance in China during 2021 to monitor the evolution of influenza viruses in poultry. A total of 35 influenza viruses were obtained in chickens, ducks, and geese, of which 30 H5N8 viruses, 3 H5N1 viruses, and 2 H5N6 viruses. Phylogenetic analysis suggested all of H5N1, H5N6, and H5N8 isolates were derived from clade 2.3.4.4b H5N8 viruses during 2020/21 season, and notably, the internal genes of H5N1 and H5N6 viruses shared different genetic heterogeneity with H5N8 viruses and had been reassorted with wild bird-origin H5N1 viruses from Europe. By contrast, almost all H5N8 viruses exhibited only one phylogenic cluster with wild bird-origin H5N8 viruses in China and Korea, indicating that H5N8 viruses in China were more stable. Besides, we found that Korea is the main output geographic location in the spread of these H5N8 viruses to northern and eastern China, and especially, the co-circulation of H5N8 viruses occurred within China, with central China acted as a seeding population during the H5N8 epidemic. The statistical support was strong for viral migration from wild birds to chickens and ducks, indicating that 2.3.4.4b poultry-origin H5N8 viruses during 2020–2021 were originated from wild birds. Our findings provide novel insights into evolution and transmission dynamics of H5 subtype influenza viruses among poultry after novel H5N8 viruses invaded China for nearly one year.